Absent Labial Frenulum in Holoprosencephaly - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Absence of the superior labial frenulum is reported in 88% of 17 consecutive cases of holoprosencephaly examined at St Christopher's Hospital for Children, Philadelphia, PA.